1999
DOI: 10.1002/(sici)1097-4636(1999)48:6<765::aid-jbm1>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Improved wettability of an experimental silicone rubber denture soft lining material

Abstract: The purpose of this study was to improve the wettability of an experimental silicone rubber soft lining material (Sildent) to increase patient comfort. Sildent was modified by the addition of polyalkylene oxide poly(dimethylsiloxane) surfactants. The various surfactants were added directly to the polymeric matrix in the quantities 5, 10, 20% w/w. The surfactants were also added to a one part silicone sealant, which was then painted onto the surface of already cured Sildent. Contact angle measurements were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Contact angle of denture soft lining materials is clinically significant as it is related to retention and patient comfort. 28 For this reason, surface treatments or cleansing agents which increase the contact angle are not considered favourable, as this might negatively affect function. The contact angles of the unmodified and coated silicones (mean 108.58, range 102.3-119.18), were similar to other contact angle measurements of silicone soft lining materials (mean 112.08).…”
Section: Characterisation Of Materialsmentioning
confidence: 87%
“…Contact angle of denture soft lining materials is clinically significant as it is related to retention and patient comfort. 28 For this reason, surface treatments or cleansing agents which increase the contact angle are not considered favourable, as this might negatively affect function. The contact angles of the unmodified and coated silicones (mean 108.58, range 102.3-119.18), were similar to other contact angle measurements of silicone soft lining materials (mean 112.08).…”
Section: Characterisation Of Materialsmentioning
confidence: 87%
“…Polyalkylene oxide surfactants, similar to other surfactants used with PVS materials, contain hydrophilic regions (alkylene oxide) and hydrophobic regions (siloxane). 22 The hydrophobic region of the surfactant allows it to be dispersible in the silicone matrix while the hydrophilic region allows interaction with water. 20 If the surfactant is too low in molecular weight and too hydrophilic, it may diffuse from the impression material into the aqueous phase of the adherent.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in an initial improvement in wettability. 22 The results of this study demonstrate that the novel surfactants in the modified PVS cause a significant decrease in the contact angle produced with water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have therefore focused on modifying the denture base to be hydrophilic to prevent hydrophobic interaction 11,14) . One promising approach is the use of coating materials because these do not change the bulk properties of the denture base material but can modify the surface properties 15,16) . Although a previous study indicated that a silica coating agent can make the denture base material hydrophilic 17) , the durability of the agent has not been clarified.…”
Section: Introductionmentioning
confidence: 99%